Oscillation criteria for a class of fractional dynamic equations on time scales - Hongxia Wang; Qinghua Feng (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In this paper, we investigate oscillation for a class of fractional dynamic equations with damping term on time scales, and establish some oscillation criteria for it. The established oscillation criteria unify continuous and discrete analysis, and are new results so far in the literature.